O3-S5.01 Impact of AIC316, a novel antiviral helicase-primase inhibitor, on genital HSV shedding: randomised, double-blind, placebo-controlled trial. (10th July 2011) - Wald, A; Stoelben, S; Tyring, S; Warren, T; Johnston, C; Huang, M L; Timmler, B; Ruebsamen-Schaeff, H; Corey, L; Birkmann, A
Abstract : Background: Current treatments for HSV infection are imperfect, do not completely abrogate viral shedding or transmission, and do not interrupt HSV-2—HIV interactions. AIC316 is a helicase-primase inhibitor, a new class of anti-HSV compounds that has a distinct mode of action from currently available nucleoside analogues. Methods: We investigated the safety and efficacy of AIC316 in patients with genital HSV-2 infection in a Phase 2, randomised, multicenter, parallel, double-blind, placebo-controlled trial of 4 different doses of AIC316 administered orally for 4 weeks. Participants were randomised 1:1:1:1:1 to one of the following dose groups: 5 mg given once daily (qd), 25 mg qd, 75 mg qd, 400 mg given once-a-week, or matching placebo. Participants in the once daily dose groups received a loading dose. During the trial period participants obtained a swab of genital secretions daily and maintained a diary of genital lesions. The primary endpoint was the rate of genital HSV shedding measured by HSV DNA PCR in the AIC316 groups vs placebo. Results: 156 (105 women and 51 men) healthy, immunocompetent, HSV-2 positive participants with a history of 1–9 recurrences per year prior to trial entry, or previous suppressive therapy, were randomised by seven US sites between May 2010 and October 2010. 147 completed the trial. Overall, about 9000 swabs for HSV PCR were collected and assayed for HSV DNA by a sensitive and accurate assay that can detect >150 copies/ml. The first results of these assessments will be presented. Conclusion: The trial will provide insight into the antiviral activity of the novel agent AIC316 for genital HSV infections. This trial design presents a robust and efficient method for evaluating antiviral activity of candidate agents for mucocutaneous HSV infections. These initial efficacy and safety results will lead to selecting the dose for further trials with AIC316.